Integrative and instrumental reminiscence therapies for the treatment of depression in older adults. - Watt, Lisa Maureen. (University of Ottawa (Canada), 1996)
Reminiscence has been identified as an important contributor to adaptation in later life by gerontologists (e.g., Birren, 1991), developmental theorists (e.g., Erikson, 1980), and clinical practitioners (e.g., Haight, 1991). Despite its wide acceptance as a therapeutic intervention, little is known about how, and for whom, reminiscence acts to produce therapeutic gains. To understand and to evaluate the therapeutic value of reminiscence for a specific clinical problem, contemporary cognitive theories of depression were integrated with reminiscence theory to develop a model that: (a) identifies the key therapeutic content of two types of reminiscence theory to interventions (integrative and instrumental); and, (b) elucidates the cognitive and emotional change processes evoked in participants of reminiscence therapy that can treat depression. Based on this model, standardized integrative and instrumental reminiscence interventions were developed and implemented with 26 older adults with moderate to severe depression. Using a clinical intervention single case study replication design, results support the utility of the model developed to explain how reminiscence contributes to the treatment of depression. In the Integrative group, constructive reappraisal of initial interpretations and emotional reactions to past self-defining events led to an improvement in self-esteem, purpose, and personal meaning, and a decline in hopelessness and internal, stable, and global attributions for the causes of negative events. In the Instrumental group, memories were used to remove emotional and cognitive barriers to coping by normalizing stress, identifying important needs at stake in current coping, providing evidence of successful past coping, and identifying appropriate coping strategies. As a result, self-esteem, life control, and problem-focused coping increased, and appraisals of stressors as threatening and unchangeable, and escape-avoidance coping decreased. Evaluation of the effectiveness of integrative and instrumental reminiscence interventions demonstrated greater clinically significant improvement in symptoms of depression in the Integrative and Instrumental groups compared with the Active Socialization Control group. In the Integrative group, 58% of clients demonstrated clinically significant improvement at post-test, yielding an effect size (ES) of.86. At follow-up, 100% of Integrative subjects improved clinically (ES =.96). In the Instrumental group, 56% of clients demonstrated clinically significant improvement at post-test (ES =.81) and 88% improved at three-month follow-up (ES =.89).
Keywords: Gerontology.